The Analysis of Criminal Sanctions Effectiveness in Drug Law: Between Prevention and Rehabilitation - Andri Winjaya Laksana; Denny Suwondo; Siti Fatimah (UNISSULA, 2026)
The purpose of this study is to analyze the effectiveness of the ideal formulation of criminal sanctions for drug addicts. Narcotics regulations were introduced as a legislative effort to replace previous laws, by regulating narcotics classification, strict supervision, as well as criminal sanctions and rehabilitative approaches. However, the effective implementation of this law still faces serious challenges, ranging from weak coordination between authorities, the type of research using normative juridical, research results indicating inconsistent law enforcement, and a lack of rehabilitation facilities, so that drug users are more often punished than rehabilitated. The lack of clarity in distinguishing users from dealers obscures the criminal justice system and exacerbates the problem of prison overcrowding. Therefore, law enforcement efforts against drug abuse must be evaluated holistically and consistently, not only in a repressive manner, but also prioritizing restorative justice, a public health approach, and social recovery as part of an integral policy to address the drug problem in Indonesia comprehensively and fairly.